Efficacy and safety of third-line or later-line targeted treatment for patients with metastatic colorectal cancer: a meta-analysis - Xue, Wen-Hui; Li, Xue-Wei; Ding, Ya-Qian; Wu, Na; Pei, Bei-Bei; Ma, Xiao-Yan; Xie, Jun; Yang, Wen-Hui (Frontiers in Oncology, 2023)
Targeted therapy has been standardized in front-line therapies for metastatic colorectal cancer (mCRC), while explicit recom-mendations for third- or later-line are still lacking. This study evaluated the efficacy and safety of combining targeted therapy with chemotherapy in the third- or later-line treatment for mCRC via meta-analysis, providing evidence-based guidance for clinical or research practice. Comprehensive retrieval of related studies was conducted according to the PRISMA guideline. Studies were stratified with patient characteristics and pharmacological classification of the drugs. For the data available for quantitative analysis, pooled overall response rate, disease control rate, hazard ratios (HR) for overall survival (OS) and PFS, and adverse events rate with respective 95% confidence intervals (CIs) were calculated. A total of 22 studies (1866 patients) were included in this meta-analysis. Data from 17 studies (1769 patients) involving targets of EGFR and VEGF were extracted for meta-analyses. The overall response rates for monotherapy and combined therapy were 4% (95% CI: 3%, 5%) and 20% (95% CI: 11%, 29%). The pooled HRs (combined therapy vs. mono) for OS and PFS were 0.72 (95% CI: 0.53, 0.99) and 0.34 (95% CI: 0.26, 0.45). Another five studies were included in narrative depiction, involving targets of BRAF, HER-2, ROS1, and NTRK. The findings of this meta-analysis indicate that VEGF and EGFR inhibitors manifest promising clinical response rates and prolonged survival in the treatment of mCRC with acceptable adverse events.